2007
DOI: 10.1002/cphc.200700084
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Size, Three‐Dimensional Shape, and Specific Surface Area of Anatase Nanocrystals

Abstract: At the heart of photocatalysis lies the recognition that chemical reactions are catalyzed on specific surfaces of catalyst particles. Because of the specific structure of such particles and the coordination of exposed surface atoms, the reactivity of different surfaces and their mechanisms for bonding to adsorbed molecules can vary dramatically. [1,2] Information about the size and shape of titanium dioxide (TiO 2 ) nanocrystals and, in particular, about the abundance and relative surface areas of specific cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The lattice parameters and the atom positions in the bulk of the cluster were fixed to the values obtained from the previous three-dimensional calculation (CCM-3D) [2]. The (1 0 0) and (1 1 0) planes for anatase and rutile, respectively, were used as representative surfaces according to respective high resolution transmission electron microscopy (HRTEM) [9] investigations.…”
Section: Theoretical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice parameters and the atom positions in the bulk of the cluster were fixed to the values obtained from the previous three-dimensional calculation (CCM-3D) [2]. The (1 0 0) and (1 1 0) planes for anatase and rutile, respectively, were used as representative surfaces according to respective high resolution transmission electron microscopy (HRTEM) [9] investigations.…”
Section: Theoretical Proceduresmentioning
confidence: 99%
“…In particular, when working with nanoparticles, the detailed knowledge of the nature of the exposed facets and of the atomic structure of the nanoparticles is of utmost interest due to their key role in the photocatalytic reaction mechanism [7,8]. Since, in particular, commercially produced TiO 2 nanocrystallites do not exhibit the equilibrium faces naturally occurring in macroscopic single crystals [9], photocatalytic reaction models assuming the well-known crystallographic facets may be unrealistic. Different exposed surfaces will definitively lead to different chemical interactions with a given adsorbate [1,2] due to a different coordination of the surface atoms, thus likely triggering different reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anatase phase of titanium dioxide enjoys more relevance as photocatalyst due to its generally higher photocatalytic activity. [45][46][47][48] The (101) facet of anatase is found to be thermodynamically favorable. However, the high reactivity of anatase nanoparticles has been often associated with the minority (001), 49 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The surfaces were modeled by finite neutral TiO 2 clusters where the peripheral oxygen atoms not belonging to the surface were saturated with hydrogen.…”
Section: Model and Computational Detailsmentioning
confidence: 96%
“…Relative stability of various low-index surfaces of anatase nanoparticles might be controlled by surface chemistry such as pH environment or hydroxilation, or particle size. 17,18 Another recent study showed that single-crystal anatase TiO 2 with a high percentage ͑001͒ surface can be synthesized by using hydrofluoric acid as a morphology controlling agent. 19 Furthermore, fluorated anatase surface can be easily cleaned to obtain fluorine free surface without altering the crystal structure and morphology.…”
Section: Introductionmentioning
confidence: 99%